2010
DOI: 10.1111/j.1463-1326.2010.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of insulin lispro protamine suspension or insulin glargine to oral type 2 diabetes regimens: a randomized trial

Abstract: At endpoint, ILPS was non-inferior to glargine in HbA1c change from baseline, but associated with increased risk of hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 10 publications
1
30
1
Order By: Relevance
“…In addition, this inhibitory action can induce mild osmotic diuresis and increase urinary excretion of glucose with modest caloric elimination leading to weight loss (2,3). Dapagliflozin, an SGLT2 inhibitor (4), has been shown to improve glycemic control in patients with type 2 diabetes as monotherapy (5) and in combination with metformin (6), sulfonylurea (7), or insulin (8), but not yet with a thiazolidinedione.…”
mentioning
confidence: 99%
“…In addition, this inhibitory action can induce mild osmotic diuresis and increase urinary excretion of glucose with modest caloric elimination leading to weight loss (2,3). Dapagliflozin, an SGLT2 inhibitor (4), has been shown to improve glycemic control in patients with type 2 diabetes as monotherapy (5) and in combination with metformin (6), sulfonylurea (7), or insulin (8), but not yet with a thiazolidinedione.…”
mentioning
confidence: 99%
“…Of the five potentially relevant trials, one was excluded because it compared ILPS with glargine in a basal-bolus insulin regimen. In conclusion, four studies comparing treatment with ILPS with treatment with insulin glargine or detemir in persons with type 2 diabetes were examined as full text (1720) (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We did not investigate publication bias using graphical or statistical methods owing to the small number of trials; accordingly, the power of these methods is limited and results from such analyses should be treated with considerable caution (16). We planned to perform three sensitivity analyses in order to explore the influence of the following factor on effect size: by repeating the analysis including patients who took a once-daily insulin dose, as in two studies (17,18), an additional daily insulin ILPS injection could be added by the study personnel, excluding the study of Arakaki et al (19) reported in abstract form and including the three studies comparing ILPS with glargine (17,19,20). P values <0.05 were considered significant, and all reported P values are two sided.…”
Section: Methodsmentioning
confidence: 99%
“…The 24-week open-label trial by Strojek and colleagues [Strojek et al 2010] compared ILPS once or twice daily versus glargine once daily. Glycemic control and overall incidence of hypoglycemia were similar.…”
Section: Comparison Of Ilps With Other Long-acting Analogsmentioning
confidence: 99%